Pemberian Health Education Salt Dietary terhadap Pasien Hipertensi di Kabupaten Majene - Muzakkir; Hermin Husaeni; Amriati Mutmainna; Ika Muzdaliah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Hypertensives in Majene regency should follow a low-salt diet. A low-salt diet is important for self-management in hypertensive patients. Lack of knowledge, attitudes, and strategies for low-salt diets in hypertensives is important for hypertensives. The community service team conducted this community service to increase knowledge, attitudes, and health education interventions regarding low-salt diets for hypertensive patients. Health education on low-salt diets is needed to influence low-salt eating behaviors in hypertensive patients. The method used is a quantitative survey with a pre-post test design approach. The analysis used was the paired t-test. The results obtained showed that there was an effect of providing health education on dietary salt to hypertensive patients in Majene Regency with a value p of 0.000, where the value p<α (α = 0.05). Suggestions for the use of salt in daily life by health-educated respondents.